In situ detection of activated Bruton’s tyrosine kinase in the Ig signaling complex by phosphopeptide-specific monoclonal antibodies - Nisitani, Sazuku (The National Academy of Sciences, 1999)
Bruton’s tyrosine kinase (Btk) is a critical transducer of signals originating from the B cell antigen receptor (BCR). Dosage, sequential phosphorylation, and protein interactions are interdependent mechanisms influencing Btk function. Phosphopeptide-specific mAbs recognizing two distinct phosphotyrosine modifications were used to quantify Btk activation by immunofluorescent techniques during B cell stimulation. In a population of cultured B cells stimulated by BCR crosslinking and analyzed by flow cytometry, transient phosphorylation of the regulatory Btk tyrosine residues (551Y and 223Y) was detected. The kinetics of phosphorylation of the residues were temporally distinct. Tyrosine 551, a transactivating substrate site for Src-family kinases, was maximally phosphorylated within ≈30 seconds of stimulation as monitored by flow cytometry. Tyrosine 223, an autophosphorylation site within the SH3 domain, was maximally phosphorylated at ≈5 minutes. Btk returned to a low tyrosine phosphorylation level within 30 minutes, despite persistent elevation of global tyrosine phosphorylation. Colocalization of activated Btk molecules with the crosslinked BCR signaling complex was observed to coincide with the period of maximal Btk tyrosine phosphorylation when stimulated B cells were analyzed with confocal microscopy. The results of these in situ temporal and spatial analyses imply that Btk signaling occurs in the region of the Ig receptor signaling complex, suggesting a similar location for downstream targets of its activity.